The Effects of a Health Literacy Enhancement Program on Health Literacy and Health Behavior to Slow Progressive Renal Failure in among Hypertension and Diabetes Mellitus Disease - Chinnoros, Somporn; Chongjarearn, Angkana; Sinraparattanaporn, Prim (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental research, two-group pretest-post test design. Aimed to study the effects of a health literacy enhancement program on health literacy and health behavior to slow progressive renal failure among hypertension and diabetes mellitus patients. The participant was purposive sampling from adulthood to elderly patients who had been diagnosed with hypertension and diabetes mellitus for more than one year, 80 participants were divided into a control group (n=40) and an experimental group (n=40). The experimental group received the 8-week health literacy enhancement program. Data collection instruments consisted of a health literacy questionnaire and a health behavior questionnaire related to delaying kidney deterioration. The reliability coefficients of these questionnaires were 0.89 and 0.88. Data were analyzed using descriptive statistics and t-tests. The research results revealed that after the trial, the experimental group had significantly higher mean scores for health literacy related to delaying kidney deterioration compared to the control group (p<.01). Additionally, the experimental group demonstrated significantly higher mean scores for health behaviors related to delaying kidney deterioration compared to the control group (p<.01). This program can be applied in teaching, nursing practice, and patient care to develop and enhance health literacy among patients with non-communicable diseases (NCDs) who are at risk of developing chronic kidney disease, thus preventing the progression to end-stage renal disease.